A novel approach to decision making of Mined Data using Dynamic Snapshot Pattern Recognition Algorithm (DS-PRA) - Iskandarani, Mahmoud Zaki (Transactions on Engineering and Computing Sciences, 2014)
A new approach to pattern recognition and decision machines profiling is proposed, proved and tested. The technique adopts the Snapshot method dynamically as a function of both organization policy and the organization departments policies. Such policies are associated with individual products and services provided by the organization with departments policies derived from general organization profile with the organization policy being a function of the various departments profiles. It is proved through real data the ability of such algorithm to classify, detect and predict policy changes and identify differences between different organizations. Also, such algorithm combines the concepts of general Artificial intelligence through the use of knowledge bases and Neural Networks by utilizing a similar weights matrix.